Pengaruh Coaching Keperawatan Terhadap Kepatuhan Perawat Melakukan Cuci Tangan Sesuai Prinsip 5 Momen 6 Langkah Di Ruang Rawat Inap Rumah Sakit Umum Daerah Kabupaten Klungkung - yanti dewi, ketut hendra; Suyasa, I Gede Putu Darma; Rismawan, Made (Jurnal Riset Kesehatan Nasional, 2017)
Background: Five Moments for Hand Hygiene is an important moment to wash hands 5 on health care providers to optimize hand hygiene by washing hands. Coaching methods can be used to improve the quality of nursing resources that will ultimately improve the quality of nursing care provided to patients through obedience perform appropriate hand washing moments principles 5 6 steps. The result of the application of the five moment in the inpatient unit District General Hospital Klungkung still below the average of the minimum service standards (SPM) is as much as> 80%. While the percentage of data compliance officer in performing hand hygiene is the nurse as much as 63.3%.Objective: the purpose of this study was to determine the effect of nursing coaching to compliance nurses perform appropriate hand washing moments principles 5 6 steps in the inpatient unit District General Hospital KlungkungMethods: This study uses an experimental approach to design pre One group pre test-posttest design. The sampling technique used is Non-Probability Sampling with consecutive sampling technique. Number samples are 63 respondents, gathering data using questionnaires.Results demonstrate compliance nurses perform appropriate hand washing moments principles 5 6 steps before nursing coaching mostly 31 people (49.2%) in the category enough. Compliance nurses do wash their hands according to the principles 5 6 moments after the steps carried out the majority of nursing coaching 58 people (92.1%) in both categories Statistical test results obtained Wilcoxon signed rank test P = 0.000 <Î± 0.05 indicates no influence on the nursing coaching compliance nurses perform appropriate hand washing moments principles 5 6 steps in the inpatient unit District General Hospital Klungkung.Conclusion: No effect on adherence nurse nursing coaching perform appropriate hand washing moments principles 5 6 steps in the inpatient unit District General Hospital Klungkung.Â Keywords: Coaching Nursing, Compliance, Hand Wash